PENGARUH KOMPETENSI BAHASA ASING TERHADAP KAPABILITAS EKONOMI LULUSAN PERGURUAN TINGGI DI PASAR TENAGA KERJA - sugito, sugito; faizin, khoirul (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study investigates the empirical link between foreign language proficiency and the economic competitiveness of Indonesian university graduates. The shift to a knowledge-based economy demands skills beyond technical expertise. Utilizing a mixed-method approach, the study surveyed 20 graduates from the 2023–2024 cohort to analyze their economic outcomes. Findings reveal a strong correlation: graduates with high foreign language skills (TOEFL > 550) secure jobs faster (1–3 months), with higher salaries (Rp9–15 million), and more strategic positions. In contrast, those with low proficiency wait longer (7–10 months) and receive lower pay (Rp4–5 million) in administrative roles. The results, consistent with Human Capital Theory , suggest that language skills are a significant investment that boosts a graduate's economic value. The study recommends that higher education should integrate foreign language into core curricula and promote international certification to enhance graduate competitiveness in the global job market.